Development of social innovation in digital-based services for children with special needs - Ginting, Rafael Lisinus; Irawan, Mirza; Devi, Selvia Inca; Sirait, Boimin; Munir, Abdul; Nainggolan, Elizon (Education and Social Sciences Review, 2024)
Problems often experienced by parents and teachers in their efforts to handle children with special needs include limited supporting facilities, parenting and teaching skills that parents lack mastery, and limited time for assistance. Next, we need significant changes from all parties to develop innovation that focuses on children with special needs. In carrying out this effort, it is necessary to develop a new breakthrough that involves several parties in collaboration between parents, teachers, psychologists, health workers, physical therapists and so on, which is called social innovation. The development model used is the 4 D model from Thiagarajan, namely: definition stage, design stage, development stage, dissemination. By involving experts on children with special needs, policy makers, parents, teachers and academics. It is hoped that this research will have positive benefits for the development of scientists' knowledge about digital-based social innovation for services to children with special needs.